EFFECT OF MOISTURE AND LOADING ORIENTATION ON THE MECHANICAL PROPERTIES OF SORGHUM AND MILLET - Lazaro, E. L.; Favier, J. F.; Mpanduji, S. M. (Tanzania Journal of Engineering and Technology, 2018)
Abstract